2016
DOI: 10.12945/j.aorta.2016.15.030
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Rupture Risk Assessment - A consistent and objective decision-making tool for Abdominal Aortic Aneurysm patients

Abstract: Abdominal aortic aneurysm (AAA) rupture is a local event in the aneurysm wall that naturally demands tools to assess the risk for local wall rupture. Consequently, global parameters like the maximum diameter and its expansion over time can only give very rough risk indications; therefore, they frequently fail to predict individual risk for AAA rupture. In contrast, the Biomechanical Rupture Risk Assessment (BRRA) method investigates the wall's risk for local rupture by quantitatively integrating many known AAA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 73 publications
(110 reference statements)
0
42
0
Order By: Relevance
“…Structural nonlinear finite element analysis (FEA) has been increasingly used to investigate the biomechanics of human organs, such as heart valves, ventricles, and blood vessels, for which in vivo organ geometries can be obtained from 3D imaging systems (eg, computed tomography). Since nonlinear FEA usually starts from the stress‐free state and the organs in in vivo images are often at a loaded state, organ geometries at the zero‐pressure level are needed, serving as a good approximation of the stress‐free state, for accurate stress analysis at loaded states . Methods to obtain zero‐pressure geometries may have potential applications well beyond FEA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural nonlinear finite element analysis (FEA) has been increasingly used to investigate the biomechanics of human organs, such as heart valves, ventricles, and blood vessels, for which in vivo organ geometries can be obtained from 3D imaging systems (eg, computed tomography). Since nonlinear FEA usually starts from the stress‐free state and the organs in in vivo images are often at a loaded state, organ geometries at the zero‐pressure level are needed, serving as a good approximation of the stress‐free state, for accurate stress analysis at loaded states . Methods to obtain zero‐pressure geometries may have potential applications well beyond FEA.…”
Section: Introductionmentioning
confidence: 99%
“…Since nonlinear FEA usually starts from the stress-free state and the organs in in vivo images are often at a loaded state, organ geometries at the zero-pressure level are needed, serving as a good approximation of the stress-free state, for accurate stress analysis at loaded states. 5,6 Methods to obtain zeropressure geometries may have potential applications well beyond FEA. Currently, by using 3D printing technology, a phantom model of a human organ can be built to have a patient-specific geometry reconstructed from 3D images 7 and similar mechanical properties of biological tissue.…”
Section: Introductionmentioning
confidence: 99%
“…The use of such an equivalent wall thickness seems to yield a more accurate prediction of the aneurysm rupture site. Anyway, in the case of mechanical simulations of aortic aneurysms, the assessment of wall thickness is still an open issue [Gasser, 2016], and in particular the assumption of uniform wall strength and thickness in FE models predicting aneurysm rupture seems to provide better results than using a variable wall thickness [Martufi et al, 2015]. As a matter of fact, most of the structural simulations dealing with the analysis of the deployment of endovascular devices and the consequent interaction with the arterial wall assume either an elastic wall with uniform thickness [Altnji et al, 2015, Perrin et al, 2015 or a wall represented as a rigid surface [Auricchio et al, 2013a, Cosentino et al, 2015.…”
Section: Simulation Framework: From Medical Images To the Virtual Endmentioning
confidence: 99%
“…To perform patient-specific biomechanical assessment, parameters of a failure metric (e.g., wall strength in the RPI) need to be quantified. Some studies suggested to use deterministic approaches [13,[22][23][24]. For instance, Geest et al [25] proposed a linear regression model to estimate wall strength of abdominal aortic aneurysm (AAA) from patient parameters (age, gender, maximum dimeter, family history and smoking status) and local parameters (local intraluminal thrombus (ILT) thickness and local diameter).…”
Section: Introductionmentioning
confidence: 99%